Back to the Future. ISPI Report 2023 - Colombo, Alessandro; Magri, Paolo (ISPI Publications, 2023)
Russia's invasion of Ukraine has upset the geopolitical balance in Europe, with shockwaves hitting the entire world. As a result, today's world seems to be heading back to a future that looks all too like countless "pasts". The mindset of "opposing blocs" is returning to Europe, or so it seems. NATO is rediscovering its identity after 30 years of drift. There is a resurgence of "non-aligned" countries, from Turkey to India, to many Latin American governments, as they seek a tricky balance between the major players. The mix of high inflation and energy crisis has taken to the stage again, dragging us back to the 1970s, when rationing and double-digit price rises were commonplace. And the nuclear threat, poverty and perhaps the risk of a less globalised world are rising too. All these returns and revivals are crucial changes that are taking their toll on Europe. The ISPI Report 2023 provides a compass to navigate this changing world.